Issues and challenges in early childhood care and education centre registration process: What the operators say? - Chin, Tong Hoey; Bing, Chan Yi; Dhamotharan, Mogana; Che Mustafa, Mazlina (Southeast Asia Early Childhood Journal, 2021)
Early Childhood Care and Education (ECCE) centre registration is an important aspect in promoting quality ECCE. Quality ECCE plays an important role in promoting holistic development for children. In the Malaysian context, ECCE is managed under a dichotomous system which is overseen by the Ministry of Women, Family and Community Development and the Ministry of Education. The ECCE registration process involves various departments, and hence, the operators need to deal with different authorities in adherence with the rules and regulations set by each authority. The objectives of this study are to explore the perceptions of the ECCE operators on the centre registration process and to investigate the challenges faced by them in the registration process. This study adopted a mixed-method research which involves 127 respondents in the survey and 53 participants in focus group interviews. The quantitative and qualitative data were analysed using SPSS and NVivo respectively. From the findings, the operators showed high awareness of the registration guidelines and the consequences of non-registration. They also highlighted concerns in terms of the clarity of the policy information for centre registration, as well as challenges faced in the registration process. The quantitative findings were further supported by the qualitative findings, whereby the operators revealed the challenges faced in the complex ECCE centre registration process as well as the inconsistent requirements for registration. Hence, shared responsibility and effective coordination should be further looked at, in the continuous efforts in promoting quality ECCE.